Institutionalization of social rights in the European Union: analysis of trends of standardization - Hretska-Myrgorodska , V. V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The purpose of this study is to identify trends in the process of institutionalization of social rights in the European Union. This paper provides an overview of documents that institutionalize standards of social rights in the European Union; systematization of standards of social rights in these documents; an analysis of recent changes to the standards proclaimed in the European Social Funds 2017; analysis of dynamics, changes in the structure of social rights and identification of characteristic features. The period of observation is years from 1951 (the first adoption of the European Social Charter) until 2017 (adoption of the document "European Foundations of Social Rights").In the course of the study it has been discovered that the list of standards is expanding with an adoption of a new document while a speed of growth in the number of standards with time is increasing. Extensions and refinement of standards are mainly carried out at the expense of general labor and social rights. The most stable dynamics has the list of standards of protection of separate classes of population. The most important part of social rights standards during the analyzed period is the set of employees’ rights and the working conditions.There search was conducted on the basis of official documents of the Council of Europe and the European Union. The results of the study may be used as an example of formation of social standards in the countries where socially oriented economy is not formed. It is oriented primarily at the non-European Union countries which have an external European integration vector. Succession of institutionalization of social standards in the European Union is a benchmark for development of a socially-oriented economy in one’s own country.